The Role of Networks in Opportunity Identification: A Focus on African Transnational Entrepreneurs - Aluko, Olu; Siwale, Juliana; Simba, Amon; Mswaka, Walter (Senate Hall, 2019)
There is a growing body of work which highlights the importance of Transnational Entrepreneurs (TEs) as catalysts for economic development in both their home and host countries. However, their opportunity identification predispositions are less understood. Thus, this study explores the nature and practices of TEs of African origin and it also focuses on how they identify viable business opportunities in their host countries. In addition, the study defines the role networks play in assisting them to achieve their business objectives. Through its application of social network constructs for data collection and analysis, this study contributes to the ongoing discourse on TEs. Specifically, it provides new insights into the way TEs of African origin living in the UK identify and exploit business opportunities. Its key findings indicate that the human capital of TEs (in particular their host country work experience), their active search, and their use of family and kinship networks underpins the way they identify viable business opportunities in a foreign country. However, perhaps the most remarkable finding of this study is that, while TEs employ both formal and informal network ties in their host countries, they seem to rely exclusively on their informal networks in their home countries.
Keywords: transnational entrepreneurs|opportunity identification|network ties|african entrepreneurs|migrant entrepreneurship